THEROLEOFDIETARYFIBERSINTHEPREVENTIONANDPROMOTIONOF CANCER - MSyedMohamedMahsooqSiddiqe; PrabuD; GibbsonDerickD; RajmohanM; Dinesh Dhamodhar; SindhuR; LubnaFathima; ERagavapriya (The Bioscan, 2025)
Cancerposesasignificanthealthissueglobally,withdietaryandlifestylechoicesplayingacrucial role.Dietaryfiber,whichispresent inplant-basedfoodssuchas fruits, vegetables, andwholegrains,hasbeen extensivelyresearchedfor itspotentialprotectivebenefitsagainstcancer,especiallycolorectalcancer.Fibermay lowercancer riskbysupportinghealthybowel function,decreasingthetimeit takesfor foodtopassthroughthe intestines, and aiding in the removal of carcinogens.Moreover, the fermentationof fiber bygutmicrobiota generates short-chain fatty acids like butyrate, known for their anti-inflammatory and anti-cancer properties. Nevertheless,someresearchindicatesthatboththetypeandquantityoffibercanaffect theseoutcomesinvarious ways,highlightingtheintricaterelationshipbetweenfiberconsumptionandcancerdevelopment.